PERANAN PENGAWAS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN SDN DI KECAMATAN RUMBIO JAYA - Badani Badani; M. Nur Mustafa; Hasnah Faizah AR (Universitas Riau, 2020)
The purpose of this paper is to know the role of school supervisor in inspecting, Advising, Monitoring, Reporting, Coordnating (Coordinating), Performing Leadership (in leading and performing the five main tasks), in improve the quality of education as in SDN. And the factors causing the gap and the effort to eliminate the gap factors in the implementation of the role of school supervision in improving the quality of education in the SDN. Efforts to eliminate the causes of gaps in the implementation of school supervisors in improving the quality of education in SDN. To study it the authors use a qualitative approach with mixed data collection techniques or mix method. It is expected that school supervisors can perform their role in the effort to improve the quality of education in the schools they supervise.